Effect of anxiety on memory for emotional information in older adults. (3rd April 2017) - Herrera, Sara; Montorio, Ignacio; Cabrera, Isabel
Abstract : Background: Several studies have shown that anxiety is associated with a better memory of negative events. However, this anxiety-related memory bias has not been studied in the elderly, in which there is a preferential processing of positive information. Objectives: To study the effect of anxiety in a recognition task and an autobiographical memory task in 102 older adults with high and low levels of trait anxiety. Method: Negative, positive and neutral pictures were used in the recognition task. In the autobiographical memory task, memories of the participants' lives were recorded, how they felt when thinking about them, and the personal relevance of these memories. Results: In the recognition task, no anxiety-related bias was found toward negative information. Individuals with high trait anxiety were found to remember less positive pictures than those with low trait anxiety. In the autobiographical memory task, both groups remembered negative and positive events equally. However, people with high trait anxiety remembered life experiences with more negative emotions, especially when remembering negative events. Individuals with low trait anxiety tended to feel more positive emotions when remembering their life experiences and most of these referred to feeling positive emotions when remembering negative events. Conclusions: Older adults with anxiety tend to recognize less positive information and to present more negative emotions when remembering life events; while individuals without anxiety have a more positive experience of negative memories.